Oral administration of hepcidin and chitosan benefits growth, immunity, and gut microbiota in grass carp (Ctenopharyngodon idella) - Zhou, Jiancheng; Feng, Mengzhen; Zhang, Weixiang; Kuang, Rui; Zou, Qi; Su, Jianguo; Yuan, Gailing (Frontiers in Immunology, 2022)
Intensive high-density culture patterns are causing an increasing number of bacterial diseases in fish. Hepcidin links iron metabolism with innate immunity in the process of resisting bacterial infection. In this study, the antibacterial effect of the combination of hepcidin (Cihep) and chitosan (CS) against Flavobacterium columnare was investigated. The dosing regimen was also optimized by adopting a feeding schedule of every three days and every seven days. After 56 days of feeding experiment, grass carp growth, immunity, and gut microbiota were tested. In vitro experiments, Cihep and CS can regulate iron metabolism and antibacterial activity, and that the combination of Cihep and CS had the best protective effect. In vivo experiments, Cihep and CS can improve the growth index of grass carp. After challenge with Flavobacterium columnare, the highest survival rate was observed in the Cihep+CS-3d group. By serum biochemical indicators assay and Prussian blue staining, Cihep and CS can increase iron accumulation and decrease serum iron levels. The contents of lysozyme and superoxide dismutase in Cihep+CS-3d group increased significantly. Meanwhile, Cihep and CS can significantly reduce the pathological damage of gill tissue. The 16S rRNA sequencing results showed that Cihep and CS can significantly increase the abundance and diversity of grass carp gut microbiota. These results indicated that the protective effect of consecutive 3-day feeding followed by a 3-day interval was better than that of consecutive 7-day feeding followed by a 7-day interval, and that the protective effect of Cihep in combination with chitosan was better than that of Cihep alone. Our findings optimize the feeding pattern for better oral administration of Cihep in aquaculture.